A educação escolar bolivariana da Venezuela e o chamado socialismo do século XXI nos governos Chávez (2005-2012) - Alves, Bruna da Silva (2015)
The main objective of this bibliographic and documental research is the identification and the analysis of the theoretical-political influences of the called “Socialism of the XXI Century” in the restructuring process of the Venezuelan school system. The assumptions of this Socialism focused on the movement of creation, experimentation and consolidation of the Bolivarian Education. The educational historic of Venezuela, before Hugo Chavez’s election in 1998, was conditioned to the political and the economic situation established in the country, which, through democratic elections, held two right-wing parties in the power on an alternation regime. This political condition generated poverty and social, cultural and educational exclusion of the people, especially from the 1980s, it occurred the penetration of neoliberalism in the country, which led to a decrease of the resources for education, resulting in the abandon of the educations system, to the poorest. The democratic election of President Chavez in 1998, marks the economic policy history and also educational of Venezuela. As soon as Chavez took over and promulgated the Constitution of the Bolivarian Republic of Venezuela in 1999, occurred the re-foundation of the State, now anchored in a new democratic conceptual mark and in a participatory democracy parameter, with the popular prominence and of confronting the United States imperialism. With the reconfiguration of the political and economic context of the country, it emerged the need of forming a new social consciousness, which entailed the modification of the educational system in consonance with the historical and cultural Latin-American legacy, from political, philosophical and pedagogical authentic parameters from Bolivarian Education. The societal project, called Bolivarian Revolution, directed changes in the political, economic and social system of the country, reflecting also in the new composition of the educational system. Under the ideological, economic and legal support of the Bolivarian State, by the massive increase of financial resources to the social sectors and the elaboration of oriented documents of the revolutionary path chosen by Venezuela, of the socialist homeland construction, - 2 as the National Project Simón Bolívar – First Socialist plan. Economic and Social Development of the Nation (PPS-2007-2013); Proposal of the homeland candidate – Commander Hugo Chávez – for the Socialist Bolivarian management (2013-2019 (after his death, this document was redefined as a Second Socialist Plan); and second the United Socialist Party Program of Venezuela (USPPV), - the school education incorporates in this process the conceptual and pedagogical guidance, and the relative autonomy to become, both in the theoretical formal plan as in implemented pedagogical practices. Therefore, there was the consolidation of a socialist mark curriculum – Diseño Bolivarian National Curriculum (2007) -, followed by the officialization of Bolivarian Education in the (Ley Orgánica de Educación) (Organic law of Education), 2009. Therefore, the multiple transformations occurred in Venezuela during Chávez governments inflated and conditioned the implementation of a national system of education consistent with needs of Venezuelan people. The statistics proved that, in Chávez’s mandates, the social and educational advances were significant and would not be achieved without political will and a governmental plan and of State that covered, in full, a set of articulated and simultaneous actions in the economic, political, social and cultural spheres.